Factors associated with nurses’ ability to perform cardiopulmonary resuscitation - Asriadi Asriadi; Irma Andrianys; Imelda Appulembang; Hamzah Tasa; Erniyanti Erniyanti (Universitas 'Aisyiyah Yogyakarta, 2023)
Cardiac arrest is a major cause of death in the world, with an estimated 17.9 million people dying each year in 2019. Several factors can influence the ability of helpers to perform cardiopulmonary resuscitation. This study aims to determine the factors associated with the ability of nurses to carry out cardiopulmonary resuscitation at Labuang Baji Hospital Makassar. This study used a descriptive-analytic method with a cross-sectional approach, with a total sample of 31 people in the ICU and Baji Ateka Care room at Labuang Baji Hospital Makassar. The results of this study indicate that there is a relationship between the level of education (p-value = 0.004), tenure (p-value = 0.001), training attended (p-value = 0.017), knowledge (p-value = 0.004) with the ability of nurses to carry out Cardiopulmonary Resuscitation (CPR). The study concludes that there is a relationship between the level of education, length of service, training, and knowledge with the ability of nurses to carry out CPR in the ICU and Baji Ateka Care room at Labuang Baji Hospital, Makassar, it is hoped that the results of this study can improve the skills of nurses in carrying out CPR correctly so that patients with a cardiac arrest can be helped properly.